Anta da Casa da Moura: um monumento megalítico no Maciço Calcário de Sicó - Silva, Fernando (2017)
Casa da Moura is one of the few megalithic monuments registered in the municipality of Soure. In this monument were carried out three campaigns of archaeological excavation with the aim of contributing to the chronological and cultural knowledge of the megalithic funerary practices in the Maciço Calcário de Sicó (Serra do Rabaçal). The data compiled point to the existence of a monument with an elongated polygonal plan and short corridor, with the limestone lages planted in the marly substrate. There were scarce vestiges of the tumulus. The collected archaeological remains are scarce in ceramic and lithic fragments, however, it presents a relevant variety of human osteological remains.